Conflito e deliberação na Serra do Gandarela : pela superação de uma dicotomia - Filipe Mendes Motta (2016)
The controversy surrounding the supposed incompatibility between deliberative democracy and conflict has been called up to deny the potential of this theoretical field. The alleged consensualist nature of deliberative theory is presented by authors with different approaches, as Rancière (2004), Miguel (2014), Mouffe (2004) and Laclau and Mouffe (2015). In an attempt to question this dichotomy, from the reconstruction of an environmental controversy in the central region of Minas Gerais, we seek to understand how the conflict contributes to the emergence of deliberation – and, at the same, how deliberation and reflexivity are capable of triggering the conflict. Our analysis focuses on environmental controversy surrounding the definition of the future of Gandarela Range, a focus of diverse interests by mining groups, social movements and local population. After carrying out interviews with the actors involved, we reconstituted the dispute process on the future of Gandarela Range, bearing in mind the different moments that compose it. With a normative approach, we point out how the conflict proves to in that context, how it contributes to the emergence of public debate, of the reflectivity of those involved and, to some extent, in decision makings about the controversy. The theoretical references of this research are approaches that question the search for substantive consensus on deliberation (DRYZEK 2000; KNOPS 2007; MENDONÇA 2011), the Deliberative System approach (MANSBRIDGE 1999; GOODIN 2005; HENDRIKS 2006; MANSBRIDGE & PARKINSON et al. 2012) and readings that emphasize the links between social movements, contentions politics and public debate (DODGE 2010, 2014; HENDRIKS 2006a, 2006b; MENDONÇA & ERCAN 2013).